Analisis Kemampuan Berpikir Kritis dan Literasi Data Menggunakan Instrumen Tes Berbasis Budaya Fahombo Batu Pada Topik Hukum Newton - Yunni Dhiva Hapsary; Riki Perdana (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2026)
This study aimed to validate and examine the reliability of instruments measuring critical thinking skills and data literacy using a culture-based Fahombo test. The profiles of students’ critical thinking skills and data literacy were analyzed based on gender differences in physics learning grounded in the local culture of Fahombo Batu on the topic of Newton’s Third Law. This study employed a quantitative approach with a descriptive design. The participants consisted of 171 tenth-grade senior high school students in the Special Region of Yogyakarta who had participated in physics learning based on the local culture of Fahombo Batu, selected through purposive sampling. The instruments used were critical thinking skills and data literacy tests, whose validity and reliability were examined using the Rasch model and Cronbach’s alpha coefficient. The results indicated that students’ critical thinking skills were in the good category, with the highest achievement in the indicators of understanding (83.52), applying (79.16), and analyzing (75.38), while the indicators of evaluating (71.21) and creating (74.43) were in the moderate category. Students’ data literacy skills ranged from moderate to good, with the highest achievement in the indicators of evaluating (84.14), interpreting (81.12), and analyzing (80.32). In contrast, the indicator of using data (74.90) was in the moderate category, and comparing data (51.20) was in the very low category. Furthermore, the analysis revealed no significant differences between male and female students in both critical thinking skills and data literacy. Overall, physics learning based on the local culture of Fahombo Batu was able to provide an overview of students’ critical thinking skills and data literacy; however, improvements are still needed in higher-order thinking skills and the optimal utilization of data.